2012
DOI: 10.1136/bjsports-2012-090938
|View full text |Cite
|
Sign up to set email alerts
|

Torsional injuries of the lower limb: an analysis of the frictional torque between different types of football turf and the shoe outsole

Abstract: Important differences in rotational torques are found and could be seen as potential risk factors for torsional injuries of the lower limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…A linear relationship may exist for axial load and RT measures 41. As the load increased, the RT measurements also increased 42.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A linear relationship may exist for axial load and RT measures 41. As the load increased, the RT measurements also increased 42.…”
Section: Resultsmentioning
confidence: 92%
“…It is suggested that for a given sport, an optimal zone of traction may exist that minimises the lower limb injury risk but allows for optimal performance 41 53 54. Indeed, it is proposed that higher levels of translational traction (ie, resistance forward/back, side/side) are associated with reduced injury frequency38 and higher performance 55.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies that include multiple shoes often report larger differences among shoes than among surfaces (Bonstingl et al, 1975; Heidt et al, 1996; Villwock et al, 2009b). Therefore, it may be possible for an athlete to decrease injury risk through shoe selection (Smeets et al, 2012).…”
Section: Traction Testing On Natural and Synthetic Turfmentioning
confidence: 99%
“…9 Blade-shaped studs, also known as shark-tooth studs, are designed to promote better traction, reduced slippage and greater kicking stability. 10,11 These studs promote higher friction torque 12 and improves performance, especially in runs with change of direction, 6, 13 compared with round-shaped studs. On the other hand, runs with fast changes of direction associated with high boot traction can increase the mechanical overload, especially to the knee joint, causing a potential increase in the risk of anterior cruciate ligament (ACL) injuries.…”
Section: Introductionmentioning
confidence: 99%